Respuesta :
Answer:
The inverse of the function f(x) is h(x) = 4x + 48 ⇒ (D)
Step-by-step explanation:
To find the inverse of a function do these steps
- Replace f(x) by y
- Switch x and y
- Solve to find the new y
- Replace y by [tex]f^{-1}[/tex](x)
Let us do these steps to solve the equation
∵ f(x) = [tex]\frac{1}{4}[/tex]x - 12
→ Replace f(x) by y
∴ y = [tex]\frac{1}{4}[/tex]x - 12
→ Switch x and y
∴ x = [tex]\frac{1}{4}[/tex]y - 12
→ Add 12 to both sides
∵ x + 12 = [tex]\frac{1}{4}[/tex]y - 12 + 12
∴ x + 12 = [tex]\frac{1}{4}[/tex]y
→ Multiply each term by 4
∵ 4(x) + 4(12) = 4([tex]\frac{1}{4}[/tex]y)
∴ 4x + 48 = y
→ Switch the two sides
∴ y = 4x + 48
→ Replace y by h(x)
∴ h(x) = 4x + 48
∴ The inverse of the function f(x) is h(x) = 4x + 48
Answer:
h(x) = 4x + 48 ⇒ (D)
Step-by-step explanation:
i just did it